Migrants' Transnationality, Societal Transformation, and Locality: an Introduction. Issue 4 (21st May 2015) - Fauser, Margit; Nijenhuis, Gery
Abstract: The implications of migrants' transnational engagements for processes of change and development in the regions of origin are attracting increased attention from both policymakers and academics. Rather than addressing the positive effects of migration and transnationality on local development, this special issue suggests a focus on the relationship between this phenomenon and broader societal transformation, thereby acknowledging the renewed importance of place and locality. To this end, this introduction provides an overview of the current debate on transnational dynamics in relation to societal transformation, local development, and inequality. Central to our analysis is the way in which migrants' transnationality engages with the hierarchies that exist between and within localities, and how this reproduces social inequalities. This introduction thus also reflects the key themes that are addressed in the five papers that make up this special issue on transnational dynamics, transformation, and locality. Copyright © 2015 John Wiley & Sons, Ltd.